Midwives’ experiences of utilising personal protective equipment during the COVID-19 pandemic: a qualitative descriptive study - O'Farrell, Angela; Chatzi, Anna V.; Doody, Owen (International Journal of Infection Control, 2023)
Background: Coronavirus has placed a lot of strain on the healthcare system. As a result, major changes have occurred in the way healthcare is delivered, including pregnancy care delivery. Within the Irish healthcare system, the response to the COVID-19 pandemic has demanded frequent and ongoing adjustments to midwifery practice and the provision of personal protective equipment (PPE) and its usage have come under serious scrutiny during the COVID-19 pandemic. Aim: To explore midwives experiences of utilising PPE during the COVID-19 pandemic. Methods: A qualitative descriptive study utilising a purposive sampling of 10 midwives who participated in in-depth semi-structured interviews, highlighting their experiences of utilising PPE during the COVID-19 pandemic. Data obtained was analysed using the Braun and Clarkes framework and reported in line with the consolidated criteria for qualitative research reporting (COREQ). Results: Analysed data resulted in five themes, eight subthemes and 18 codes. The themes identified represent the participants experiences and highlight the; importance of effective communication, fear and anxiety of contracting and spreading the virus, value of peer support as a coping strategy, impact of lack of resources in the midwifery practice, and education and training effectiveness. Conclusion: The introduced strict mandatory infection prevention and control measures, predominantly the wearing of PPE, took effect with concurrent increased stress and anxiety, while caring for pregnant women.